Analysis of the Effect of Competence on the Performance of Village Planner Through the Utilization of Information Technology - Catur Subandi; Yanuar Bachtiar; Gemi Ruwanti; Nadila Deryza Syofrin; Juliandi Juliandi (AIBPM Publisher, 2022)
The purpose of this study was to determine the effect of competence on the performance of village government officials through the use of village financial applications. Research method: Quantitative using part analysis of 285 employees of the village financial system operator, village treasurer, and village planning in Pulang Pisau, Central Kalimantan. The results show that competence has a direct effect on employee performance and the use of information technology successfully mediates the relationship between competence and employee performance. Implication: Employees need to improve their skills in using technology to maximize expertise in financial planning and reporting.Â Keywords: Competence, Utilization of Technology, Employee Performance